Thematic Electronic Module Based on Al-Quran and Hadith: A development of Teaching Material at Elementary School - Hidayah, Nurul; Yanti, Yuli (JIP Jurnal Ilmiah PGMI, 2024)
The objective of this study is to create an electronic module focused on thematic Al-Qur'an and Hadith for third-grade students at Elementary School. The participants in this research were third-grade students from Madrasah Ibtidaiyah Negeri 2 Bandar Lampung, Sekolah Dasar IT Pringsewu, and Sekolah Dasar Negeri 1 Sumberejo. This development research follows the steps outlined by Branch using the ADDIE design model, which includes analysis, design, development, implementation, and evaluation. Data collection was conducted using interview guidelines, assessment sheets for the e-module product, and observation sheets for both teachers and students. Data analysis employed quantitative descriptive analysis techniques. The instrument used was an assessment scale to evaluate the module's feasibility and to gauge student responses regarding its appeal, utilizing a Likert scale formatted as a checklist. Validation results from six experts indicated that the two media experts rated the module with an average score of 90%, categorizing it as very feasible; the two material experts scored an average of 93%, also in the very feasible category; and the two language experts gave an average score of 94%, again classified as very feasible. The responses from educator I to the electronic module yielded a score of 90% (very feasible), educator II received a score of 86% (very feasible), and educator III scored 93% (very feasible). In the small group test conducted at school A, the module achieved a score of 97% in the very appropriate category, while the large-scale tests at two schools resulted in scores of 94% at school B and 96% at school C, both categorized as very appropriate. Therefore, it can be concluded that the developed electronic module aligns with the teachings of Al-Qur'an Hadith and environmental education, adheres to the national education curriculum, and is highly suitable for use as instructional material.